Microsatellite Analysis of Five Populations of Alosa braschnikowi (Borodin, 1904) Across the Southern Coast of the Caspian Sea - Jafari, Omid; Fernandes, Jorge Manuel de Oliveira; Hedayati, Ali-Akbar; Shabany, Ali; Nasrolahpourmoghadam, Maryam (Frontiers in Genetics, 2019)
Genetic diversity studies are essential in characterization of populations and species conservation. Alosa braschnikowi is a commercially valuable species native to the Caspian Sea. It is thought to have 8 to 9 subspecies but the genetics of these populations remains to be investigated. The present study was performed to evaluate the genetic population structures of Caspian marine shad (A. braschnikowi) in the southern coast of the Caspian Sea using six pairs of SSR markers. A total of A. braschnikowi 140 specimens through five locations across the southern coast of the Caspian Sea were genotyped and 130 alleles were identified. The overall mean values of Ho and He were 0.58 and 0.87, respectively, with highest and minimum value of Ho observed in Sari (0.66±0.08) and Miankaleh (0.50±0.04), respectively. The overall mean value of allelic richness was 12.6. The data suggest that there was a high rate of migration between populations of A. braschnikowi (overall mean of Nm= 8.45), with the highest value (9.89) between Sari and Miankaleh locations. AMOVA results showed that 96% of variation was related to within populations and only 4% belonged to between populations. The mean Fst value of 0.03 indicates a low level of population differentiation. Our data suggest that there may be two genetically separate populations of A. braschnikowi across the southern coast of the Caspian Sea and a high rate of migration is likely to limit genetic diversity between them.